Diseño de una estrategia educativa "lactano con amor" para madres adolescentes y sus familias en un hospital público de Bogota D.C (2024)
Purpose: Design the educational strategy “Breastfeeding with love” based on the Theory of Adoption of the maternal role - Becoming a Mother by Ramona Mercer, aimed at adolescent mothers and their families in a public hospital in Bogotá D.C. Method: The three initials of the Evidence-Based Nursing (EBE) methodology were executed, where from the formation of a clinical question, a literature review was guided that allowed us to recognize the relevant scientific evidence related to the identified problem and from An effective educational strategy was developed. The teaching aid designed was an educational digital primer that addressed central points to address the problem identified in light of the postulates of Ramona Mercer's mid-range theory. Results: The educational strategy 'Breastfeeding with Love' was designed to promote exclusive breastfeeding in adolescent mothers during the first 6 months of their children's lives in a public health institution in Bogotá D.C.